Evaluation of Clinical Skills of Family Physicians in Fars Province by Means of Observed Structured Clinical Evaluation - Hasan Joolaee; Mahvash Alizadeh; Mohammad Hossein Fallahzadeh; Ali Baseri; Mehrab Sayadi (Kerman University of Medical Sciences, 2011)
Background & Objective : Medical education provides an opportunity to train individuals for patient care Evaluation of physicians capabilities as an important part of each educational system can reflect the efficacy of Medical education curriculum and also continuous educational programs The aim of this study was to evaluate the clinical skills of family physicians in Fars/Iran by using Observed Structured Clinical Evaluation (OSCE) Methods : In this cross sectional study from a total of 320 physicians employed in the family physician project of Shiraz University of Medical Sciences 79 physicians were selected by systematic sampling and participated in 19 designed stations Data were gathered by a structured questionnaire with acceptable validity and reliability Correlation tests and ttest with significant level of 005 were used for data analysis Results : From 79 participants 49 ones (62%) were male The total OSCE score was 190 and the acquired mean score by participants was 113±15 There was a significant relationship between OSCE score and participants gender (0004) while no significant relationship was observed between OSCE score and variables of graduation place and employment status Conclusion : Poor capability of family physicians in providing good health care services requires several interventions for improving their clinical skills